2014
DOI: 10.1007/s11262-014-1153-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of swine influenza viruses in Thai swine farms, 2011–2014

Abstract: The pig is known as a "mixing vessel" for influenza A viruses. The co-circulation of multiple influenza A subtypes in pig populations can lead to novel reassortant strains. For this study, swine influenza surveillance was conducted from September 2011 to February 2014 on 46 swine farms in Thailand. In total, 78 swine influenza viruses were isolated from 2,821 nasal swabs, and 12 were selected for characterization by whole genome sequencing. Our results showed that the co-circulation of swine influenza subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…EA‐like H1N1 IAV‐S was detected in 2001 and became dominant after 2005 in China (Vijaykrishna et al., ). Reassortant IAVs‐S containing genes derived from EA‐like H1N1 IAVs‐S have been reported in Thailand since 2000 (Abe et al., ; Nonthabenjawan et al., ; Poonsuk, Sangthong, Petcharat, & Lekcharoensuk, ; Takemae et al., ), and a reassortant among EA‐like H1 IAVs‐S, North American triple reassortant (TR) IAVs‐S and A(H1N1)pdm09v was identified in South Korea in 2013 (Lee et al., ). Our previous IAVs‐S surveillance in Vietnam (from 2010 to 2015), the second‐largest pig‐producing country in Asia, detected the introduction of H1 or H3 TR IAV‐S, human seasonal H1 that had circulated before 2009 and H3N2 viruses, and A(H1N1)pdm09 viruses into the Vietnamese pig population (Takemae et al., ).…”
Section: Nucleotide Identities and Genetic Origins Of A/swine/ba Ria mentioning
confidence: 99%
“…EA‐like H1N1 IAV‐S was detected in 2001 and became dominant after 2005 in China (Vijaykrishna et al., ). Reassortant IAVs‐S containing genes derived from EA‐like H1N1 IAVs‐S have been reported in Thailand since 2000 (Abe et al., ; Nonthabenjawan et al., ; Poonsuk, Sangthong, Petcharat, & Lekcharoensuk, ; Takemae et al., ), and a reassortant among EA‐like H1 IAVs‐S, North American triple reassortant (TR) IAVs‐S and A(H1N1)pdm09v was identified in South Korea in 2013 (Lee et al., ). Our previous IAVs‐S surveillance in Vietnam (from 2010 to 2015), the second‐largest pig‐producing country in Asia, detected the introduction of H1 or H3 TR IAV‐S, human seasonal H1 that had circulated before 2009 and H3N2 viruses, and A(H1N1)pdm09 viruses into the Vietnamese pig population (Takemae et al., ).…”
Section: Nucleotide Identities and Genetic Origins Of A/swine/ba Ria mentioning
confidence: 99%
“…In this study, we conducted a longitudinal survey in a pig farm from January 2017 to November 2018. The previous study on S-IAVs in this pig farm in 2015 showed that this pig farm had been infected with S-IAVs and estimated prevalence of S-IAVs was 6.66% 5 . Comparing to previous study, the S-IAV prevalence in this study was 18.81% (from January 2017 to November 2018), which was higher than previous report in 2015.…”
Section: Discussionmentioning
confidence: 82%
“…Comparing to the previous study in Thailand during 2000-2014, three subtypes of S-IAVs were identified, but S-IAV-H1N2 could not be identified in this study. Notably, S-IAV-H1N2 has lower prevalence than S-IAV-H1N1 and S-IAV-H3N2 5,19 . Phylogenetic analysis of H1 gene showed that S-IAVs in this study as well as endemic Thai-S-IAVs belonged to www.nature.com/scientificreports/ www.nature.com/scientificreports/ the distinct sublineage 1A.1.2 of classical swine (CS) 5,9 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies reported H1N1, A(H1N1)pdm09, H1N2, and H3N2 viruses in swine exhibiting respiratory disease symptoms between 2000 to 2014. Intriguingly, one swine sample was found co-infected with four IAV subtypes including H1N1, H1N2, H3N1, and H3N2 viruses [146][147][148][149][150][151][152].…”
Section: Thailandmentioning
confidence: 99%